Pelaksanaan Lelang Parate Eksekusi Hak Tanggungan Milik Debitur Di Bank Tabungan Negara Cabang Mataram - Muhammad Imam Haroki; Hirsanuddin Hirsanuddin (Departement Business Law, Faculty of Law, University of Mataram, 2025)
This research discusses the implementation of parate execution auctions as an effort to resolve non performing loans at PT Bank Tabungan Negara (Persero) Tbk, Mataram Branch. As a state-owned bank focused on housing finance, BTN faces the risk of non-performing loans (NPL), which are addressed through credit restructuring or collateral execution. The implementation of parate execution is based on Law No. 4 of 1996 concerning Mortgage Rights and Minister of Finance Regulation No. 213/PMK.06/2020 on Auction Implementation Guidelines, which allows the bank to execute collateral without a court ruling if certain conditions are met. This research uses a normative-empirical legal method with statutory, case, and sociological approaches. Data were collected through legal document studies and interviews with BTN Mataram Branch staff. The findings indicate that collateral can only be auctioned if the debtor fails to undergo restructuring and has been issued three warning letters without response. The auction is carried out transparently through KPKNL using the e-auction system. Post-auction challenges include debtor objections and administrative issues such as the title transfer process. Although the procedures have been conducted in accordance with legal provisions, more detailed regulations are needed regarding collateral criteria and debtor protection to ensure fairness and legal certainty in the execution of parate auctions.